Association of eNOS Glu298Asp polymorphism with cardiometabolic risk and inducible myocardial ischemia in patients with stable coronary artery disease. (3rd October 2022) - Modena, M; Vecoli, C; Caselli, C; Todiere, G; Poddighe, R; Valente, S; Bandini, F; Natali, A; Ghiadoni, L; Clerico, A; Vittorini, S; Botto, N; et al.
Abstract: Background: The endothelial nitric oxide synthase (eNOS) gene deficiency is known to cause insulin resistance, hypertension, hypertriglyceridemia and impaired coronary vasodilating capability in animal models. In the general clinical population, the eNOS gene polymorphism (Glu298Asp, G894T), able to reduce eNOS activity, was associated either with features of the metabolic syndrome or prevalence of coronary artery disease (CAD). Purpose: To investigate the possible association of Glu298Asp polymorphism with cardiometabolic risk [insulin resistance, increased triglycerides (TG) and low HDL-cholesterol (HDL-C)], obstructive CAD and inducible myocardial ischemia in stable patients with suspected coronary disease. Methods: Six cardiology units enrolled a total of 506 consecutive patients (314 males; mean age 62±9 years) referred for suspected CAD within the BIOGEN-CARE Tuscan Region Italian Study. Among these, 325 patients underwent stress ECG or cardiac imaging to assess the presence of inducible ischemia and 436 patients underwent non invasive computerized tomography or invasive coronary angiography to assess the presence of obstructive CAD (>50% stenosis in at least one major coronary vessel). Blood samples were collected from each patient for genotyping and measurements of lipid and glucose parameters. The TG/HDL-C ratio and the TyG-index [ln(TG × Fasting plasma glucose/2)] were used as synthetic markers of atherogenic dyslipidemia and insulin resistance, main components of the cardiometabolic risk. Results: In the whole population, 49.6% of patients were homozygous for the G894allele, 40.9% heterozygotes, and 9.5% homozygous for T894. Myocardial ischemia was documented in 160/325 (49.2%) patients undergoing stress testing and obstructive CAD in 178/436 (40.8%) patients undergoing coronary angiography. Patients carrying the T allele (dominant model TT+GT vs GG) had higher TG/HDL ratio (2.7±1.8 vs 2.5±1.9, P=0.03) (Figure) without differences in other lipid and glucose markers. Independent predictors of obstructive CAD were age, gender, obesity, diabetes and TG/HDL-C ratio but not the the T allele (OR 0.80; CI 0.51–1.25; ns). Independent predictors of inducible ischemia were age, gender, obesity and the T allele (OR 1.91; CI 01.19–3.08; P=0.007). Stratifying the population for both obstructive CAD and ischemia, the T allele was associated with increased risk of ischemia (OR 1.96; CI 1.11–3.44; P=0.02) even after adjustment for the presence of obstructive CAD (OR 3.09; CI 1.85–5.78; P<0.001) (Figure 1). Conclusions: In stable patients with suspected CAD, the eNOS Glu298Asp gene polymorphism is an independent risk factor for inducible myocardial ischemia and is significantly associated with the specific cardiometabolic risk expressed by high TG and low HDL-C which independently predicts obstructive CAD. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): "BIOhumoral and GENetic predictors of CARdiac Evolving phenotype in Ischemic Heart Disease (BIOGENCARE-IHD)"; funded by Toscan Region-Programma per la ricerca regionale in materia di Salute 2009